2019
DOI: 10.1002/nau.24142
|View full text |Cite
|
Sign up to set email alerts
|

Urinary nerve growth factor can predict therapeutic efficacy in children with monosymptomatic nocturnal enuresis

Abstract: Aim To determine the urinary levels of nerve growth factor (NGF) and brain‐derived neurotrophic factor (BDNF) in children with monosymptomatic nocturnal enuresis (MNE) and evaluate whether these factors can be used as biomarkers for the treatment outcome. Methods NGF and BDNF levels were measured and compared in 38 children (28 boys and 10 girls) with MNE and 25 children (18 boys and 7 girls) with no urinary symptoms were assessed. The mean ages in the patient and control groups were 9 and 10 years, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 24 publications
(62 reference statements)
0
20
0
1
Order By: Relevance
“…The systolic non-dipper, diastolic non-dipper and mean non-dipper values for non-dipper patients are given in Table 1. The diagnostic age in the non-dipper group was median 8 years (7-13), with value of 10.6 years (8)(9)(10)(11)(12)(13)(14)(15) in the normal 24 h ABPM group (P < 0.05). The female / male ratio was 22/30 (0.73) in the non-dipper group and 35/28 (0.92) in the normal 24 h ABPM group (P < 0.05) (Table 2).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The systolic non-dipper, diastolic non-dipper and mean non-dipper values for non-dipper patients are given in Table 1. The diagnostic age in the non-dipper group was median 8 years (7-13), with value of 10.6 years (8)(9)(10)(11)(12)(13)(14)(15) in the normal 24 h ABPM group (P < 0.05). The female / male ratio was 22/30 (0.73) in the non-dipper group and 35/28 (0.92) in the normal 24 h ABPM group (P < 0.05) (Table 2).…”
Section: Resultsmentioning
confidence: 96%
“…For many cases of enuresis nocturna, contradictory results have been obtained about both diagnosis and treatment, just as for all studies in the scientific world. Some of these found parasympathetic activity was dominant in children with enuresis, 12,13,14 while recent studies have shown sympathetic activity and disrupted circadian rhythm in BP regulation come to the force. 4,9,15 Accordingly, if the expected physiological fall in BP does not occur, night time sodium excretion in urine and polyuria increases and nocturnal enuresis occurs.…”
Section: Discussionmentioning
confidence: 99%
“…The following experimental conditions were tested for the fine-tuning and validation of a methodology to quantify BDNF protein in human urine samples, in accordance with an appropriate QA/QC process: (i) analysis of urine samples with and without pre-treatment (acidifying, extracting and/or lyophilizing of biological samples); (ii) dilution (or not) of samples; (iii) testing of different sample volumes (range 0.1–0.8 ml); and (iv) selection of commercial ELISA kits, based on the literature ( Supplementary Table 2 ), because ELISA techniques have demonstrated good sensitivity and specificity for the evaluation of BDNF levels ( Sakamoto et al, 2018 ). The Emax ® ImmunoAssay System ELISA kit (Promega Corporation, Madison, WI, United States), one of the kits most commonly used to determine BDNF in urine samples ( Pinto et al, 2010 ; Antunes-Lopes et al, 2013 , 2017 ; Jiang et al, 2014 ; Morizawa et al, 2019 ), has been discontinued. Other ELISA kits previously used for this purpose could not be used because samples were always below their LOD, with or without pretreatment, including the Quantikine ® Total BDNF and Human BDNF ELISA kits (cat# DBNT00, cat# E-EL-H0010, and cat# EK-033-22), supplied by R&D System, Elabscience and Phoenix Pharmaceuticals, respectively ( Polacchini et al, 2015 ; Pennycuff et al, 2017 ; Rada et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…18 Recent studies have proposed several candidate biomarkers for distinguishing between MNE and NMNE. 19 Because many patients with LUTS show a small FBC, patients with NMNE also could show a small FBC. Therefore, we thought that a small FBC can be biomarkers for distinguishing between MNE and NMNE.…”
Section: Discussionmentioning
confidence: 99%